The fascistisation of social reproduction - Gago, Maria Veronica (2025)
In what follows I analyse the emergence of Milei’s ultra-right government in terms of three ideas: 1) as a reactionary response to a sequence of struggles led by feminism and its way of politicising social reproduction; 2) as the effect of a subjectivity trained in an economic crisis that is financially ‘resolved’ with debt in order to live; and 3) as the symptom of a crisis of representation of the democratic political system expressed as the right- wing’s attempt to capture radicalness. Finally, I suggest the notion of ‘fascistisation of social reproduction’ as a way to connect these ideas.